The Effect of E-CRM Implementation and E-Service Quality on Corporate Image and Customer Satisfaction and Its Impact on Customer Loyalty - Nurrohman, Rosyid; Astuti, Endang Siti; Yulianto, Edy (Profit: Jurnal Adminsitrasi Bisnis, 2023)
The purpose of this study is to explain and analyze the effect of e-CRM and e-service quality on corporate image and customer satisfaction and their impact on customer loyalty. Competition in the business world to get maximum profit every company is always trying to maintain the company's image and increase customer satisfaction in order to impact customer loyalty. e-CRM and e-service quality are breakthroughs in innovation to improve the corporate image and customer satisfaction, which will have an impact on customer loyalty. This research is an explanatory study on the number of samples obtained using the Slovin formula with 204 respondents. The sampling technique used is a random sampling technique. The analytical method used was PLS SEM. The results of this study show that the e-CRM variable has an effect, but is not significant, on customer loyalty, and the company image variable does not mediate the electronic service quality variable on customer loyalty. The practical implications obtained from this research can be used by related companies to evaluate e-CRM, e-service quality, corporate image, customer satisfaction, and customer loyalty within the company so that this research can support the company's strategy of efforts to maintain customer satisfaction and loyalty